Effectiveness of Oketani Breast Massage with Lavender Essential Oil in Enhancing Breastfeeding Success: A Quasi-Experimental Study in Rural Community - Gempi Tri Sumini; Lilis Suryani; Wahyu Anjas Sari; Dwi Retno Wati (YCAB Publisher, 2026)
Background: Breastfeeding is a critical determinant of infant health and development, yet many mothers face challenges that hinder breastfeeding success, particularly in rural settings with limited access to lactation support. Oketani breast massage and lavender essential oil aromatherapy have been explored individually for their potential to improve lactation outcomes. Objective: This study aimed to evaluate the effectiveness of Oketani breast massage combined with lavender essential oil in enhancing breastfeeding success among postpartum mothers in a rural Indonesian community. Methods: A one-group pretest-posttest quasi-experimental design was used, involving 80 postpartum mothers in Penjalian Village, East Java, Indonesia. Participants received Oketani breast massage and lavender essential oil therapy daily for seven days postpartum. Breastfeeding success was assessed using the LATCH scoring system before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test. Results: The proportion of mothers achieving a “good” LATCH score increased from 46.25% before the intervention to 72.50% after the intervention. The Wilcoxon test revealed a statistically significant improvement in breastfeeding success (Z = -4.750, p < 0.001), indicating the positive impact of the combined intervention. Conclusion: Oketani breast massage combined with lavender essential oil is an effective, low-cost, and culturally appropriate intervention to enhance breastfeeding success in postpartum mothers. Its implementation in rural communities can serve as a practical strategy to support exclusive breastfeeding practices and improve maternal-infant health outcomes. Keywords: oketani breast massage; lavender essential oil; breastfeeding success; postpartum mothers; LATCH Score